2017
DOI: 10.1007/s10903-017-0670-9
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers for Advance Care Planning Among Ethnic and Racial Minorities in the U.S.: A Systematic Review of the Current Literature

Abstract: Growing evidence suggests a low engagement in advance care planning (ACP) among ethnic minorities in the U.S. The purpose of this study was to synthesize findings from prior research about ACP among ethnic minorities. An extensive literature search was conducted using multiple electronic databases. After applying inclusion criteria, 26 studies were included. Four categories of facilitators and barriers to ACP were identified: (1) Socio-demographic factors, (2) health status, literacy and experiences, (3) cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
139
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 40 publications
19
139
0
Order By: Relevance
“…We also found independent relationships between ACP knowledge and other sociodemographic factors, including Spanish language and nonwhite race, similar to other studies . Prior studies, however, did not assess health literacy, preferred language, finances, or social support.…”
Section: Discussionsupporting
confidence: 88%
“…We also found independent relationships between ACP knowledge and other sociodemographic factors, including Spanish language and nonwhite race, similar to other studies . Prior studies, however, did not assess health literacy, preferred language, finances, or social support.…”
Section: Discussionsupporting
confidence: 88%
“…30 Familycentered decision making was also an important factor in the perceived value of ACP among African American, Latino, and Asian ethnic groups. 28,30,32,55,72,75 Family-centered decision making could affirm relationships but was also challenging. 72 The concept of filial piety (duty to one's family) may have a dual meaning, emphasizing both the need to preserve life but also to ensure patient wishes and comfort.…”
Section: Perceived Value Of Acp Discussionmentioning
confidence: 99%
“…These reviews were heterogeneous, including a range of health conditions, cultural groups, and populations. 22,26,28,29,33,34,39,44,51,53,54,56,60,62,64,66,68,73,75 In the context of dementia, ascertaining the views of people with dementia rather than reliance on proxies should be of primary concern. 48 This meant that health care professionals would need more training in ACP processes and prognostic implications of dementia to be able to confidently discuss with people with dementia and their carers.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…In our cohort of nurses with their similar education levels and healthcare backgrounds, the persistent racial differences in ACP highlight the importance of better addressing the range of factors limiting ACP participation in minorities because this limited participation may lead to EOL care that is not goal aligned . Reviews have found, particularly for older generations of African Americans, that barriers such as communication problems with physicians and mistrust of the healthcare system were obstacles for ACP engagement; our findings may indicate that such communication issues and mistrust may be deeply embedded because they persist even among former nurses, or there may be other barriers that are as yet unidentified.…”
Section: Discussionmentioning
confidence: 99%